Assessing the Collective Impact of Community Health Programs Funded by Food and Beverage Companies: A New Community-Focused Methodology. (January 2020) - Barata-Cavalcanti, Olivia; Leung, May May; Costa, Sergio; Mateo, Katrina F.; Guillermin, Michelle; Palmedo, P. C.; Crossley, Rachel; Huang, Terry T.-K.
Aims: We developed and pilot-tested a new methodology to evaluate the collective impact (CI) of food and beverage company-funded community-based programs aimed at improving nutrition and physical activity. Methods: The Collective Impact Community Assessment Scale assesses programs across 14 dimensions. Five community programs funded by five companies participated in the testing of this tool. Qualitative data were collected through in-person key informant interviews, focus groups, and direct observations of program activities. Eight interviews/focus groups (representing program management, delivery staff, participants, and community champions) were selected in each program for review and analysis using a scoring system with preestablished anchors and algorithms. Raw scores ranged on a scale from 0 to 8 for each dimension and were standardized as percentages. Dimension scores were averaged to generate a total composite score. Results: Total composite scores of CI for programs ranged from 63% to 89%. The CI dimensions that scored the highest were backbone infrastructure (median = 94%, range = 88%–100%) and common agenda (median = 91%, range = 59%–97%). All programs scored lower on dimensions related to their ability to impact funding flows (median = 47%, range = 34%–94%), cultural norms (median = 69%, range = 34%–88%), and advocacy and public policy (median = 56%, range = 25%–69%). Conclusion: Variability in CI approach scores demonstrates the tool's ability to differentiate the impact of a wide range of programs across multiple dimensions. The CI Community Assessment Scale provides a common metric platform to compare different community-based initiatives.